PENGARUH PEMBERIAN ABU BATUBARA SEBAGAI SUMBER SILIKA (SI) BAGI PERTUMBUHAN DAN PRODUKSI TANAMAN PADI (Oryza sativa L) - Teguh Budi Prasetyo; Syafrimen Yasin; Edri Yeni (Jurnal Solum, 2010)
A research about use of coal ash as a silicate source for rice production was conducted in Greenhouse at Agriculture Faculty of Andalas University from October 2006 to February 2007.  The objective of this research was to study the effect of coal fly ash as silicon (Si) sources for the growth and production rice crops (Oryza sativa L.).  The experiment was designed on Completely Randomized Block Design with four treatments and three replications.  The treatments consist of ; 0 ton/ha, 20 ton/ha , 40 ton/ha  and 60 ton/ha coal fly ash.  The result showed that, fly ash from coal burning could increase  available fosfor and reduce dissolved aluminum in the soil.  Fly ash could also increase crop production, P- and Si-absorption by crops.Key Words: coal fly ash, silicate, rice crops